Validation of ICMR Neurocognitive Toolbox for Dementia in the Linguistically Diverse Context of India - Verma, Mansi; Tripathi, Manjari; Nehra, Ashima; Paplikar, Avanthi; Varghese, Feba; Alladi, Suvarna; Narayanan, Jwala; Dhaliwal, R. S.; Sharma, Meenakshi; Saroja, Aralikatte Onkarappa; Arshad, Faheem; Divyaraj, Gollahalli; et al. (Frontiers in Neurology, 2021)
Objectives: The growing prevalence of dementia, especially in low and middle-income countries (LMICs) has raised the need for a unified cognitive screening tool that can aid its early detection. The linguistically and educationally diverse population in India contributes to challenges in diagnosis. The present study aimed to assess the validity and diagnostic accuracy of the Indian Council of Medical Research-Neurocognitive Toolbox (ICMR-NCTB), a comprehensive neuropsychological test battery adapted in five languages, for the diagnosis of dementia in its early stages. Methods: A multidisciplinary group of experts developed the ICMR-NCTB based on reviewing the existing tools and incorporation of culturally appropriate modifications. The finalized tests were then adapted and translated into five Indian languages: Hindi, Bengali, Telugu, Kannada, and Malayalam. 458 participants were recruited; including 325 controls and 133 dementia patients. Psychometric properties of the adapted tests were examined, and the sensitivity and specificity for the diagnosis of dementia and its subtypes Alzheimer’s disease (AD) and vascular dementia (VaD) were established. Results: The sensitivity of the ICMR-NCTB to identify dementia ranged from 0.91 to 0.95 across all five languages. Specificity ranged from 0.90 to 0.98 across all languages. The sensitivity and specificity of the ICMR-NCTB to identify AD were 0.88 and 0.84 respectively and for VaD: 0.83 and 0.84 respectively. Conclusions: The ICMR-NCTB is a valid instrument to diagnose dementia and its subtypes across five Indian languages, with high diagnostic accuracy. The toolbox was effective in overcoming the challenge of linguistic diversity. The study has wide implications to address the problem of a high disease burden and low diagnostic rate of dementia in LMICs like India.